(3JGQjN eOjfI aGS hHfGA LGeY GdbQhjjf hGdCfOdSjjfs ((3GdLjdGfi Hf YHO GdSdGe GdZQGHdi GdbUQi s)
(3ChdgG (B:s
(3GdMeO ddg LYd aGJMh GdcJGH s
(3BNQgG (B:s
(3aef hLO NWC adjUdM ChRddkG adjUaM hGdCeQ cdg ddg hdG Mhd hdGbhI EdG HGddg hMSHfG Gddg hcai hUdi Gddg Ydi SjOfG eMeO GdeUWai hYdi Bdg hUMHg hSde JSdjekG cKjQkG s
(3Vef eLehY s
(3de jYde eDdags
(3hjdi gPG GdcJGH ai GdeLehYI cJGH GdLZQGajGs
(3hde jYde eDdag hjTJed Ydi SHYI CLRGA cGdCLRGA GdMOjKI hgh ai (B60 (3hQbIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs